NATURAL ANTIMICROBIAL AGENT USE IN THE PRESERVATION OF FRUITS AND VEGETABLES - Sauceda, Elvia Nereyda Rodríguez (Universidad Autónoma Indígena de México, 2018)
Today has been a need to find alternatives of conservation, because it has been associated with consumption of poison chemical preservatives. The demand for minimally processed fresh products is increasing, and interest in natural antimicrobial agents (derived from plants), so now looking for the combination of two or more factors that interact additively or synergistically controlling population microbial, allowing it to fresh produce similar products with less additives, it should be noted that the rate of microbial spoilage depends not only on microorganisms but also the chemical combination of product and type of initial microbial load. That is why the main aim of food processing is to provide comfort to humans through a safe, nutritionally adequate and meet the expectations of taste, aroma and appearance, so the use of natural food additives involves the isolation, purification, stabilization and incorporation of these compounds to food antimicrobial purposes, without adversely affecting the sensory characteristics. In general, every time we discover more plants or parts thereof which contain natural antimicrobials, such as including phenolic compounds from bark, stems, leaves, flowers, organic acids present in fruits and phytoalexins produced in plants, so as will not only safer, but better food quality and type of antimicrobials that are regarded as potentially safer sources.